A Feminist Perspective: Why Feminists Should Give the Reasonable Woman Standard Another Chance - Kerns, Andrea M. (Columbia Journal of Gender and Law, 2001)
Feminists have much to celebrate over the advancement of sexual harassment law. For example, over the last thirty years sexual harassment has grown from an unrecognized claim under Title VII of the Civil Rights Act of 1964 to a discrete form of sex discrimination that violates Title VII. Moreover, an open dialogue about the sexual harassment that women encounter in the workforce has emerged in the last decade. Since the infamous Anita Hill-Clarence Thomas hearings in 1991, discussions about sexual harassment have moved out into the open from behind closed doors to discussions on Capital Hill, in the media, around office water coolers, and in the courts. But despite these successes, feminists are divided over a crucial aspect of how courts should handle this form of sex discrimination. At issue is the perspective a court should use to determine whether an employer’s or a co-worker’s behavior is sexual harassment. Specifically, should courts apply a reasonable person or a reasonable woman standard? Some feminists advocate the use of the traditional reasonable person over the reasonable woman standard because no two women share the same perspective, and because under a separate standard they will become unequal to men in the eyes of the law. Other feminists argue that it is appropriate to apply a reasonable woman standard in sexual harassment cases because that standard takes into consideration common female experiences and assesses them in light of the individual circumstances at hand. In this article, I will argue that the “reasonable woman” is the more appropriate standard for sexual harassment jurisprudence. A cause of action for sexual harassment under Title VII is “an invention of our times. The law of sexual harassment developed thanks to the efforts of feminists and activists who were determined to convince the courts that sexual coercion and harassment in the workplace is a form of sex discrimination. Today, feminists should continue to fight discrimination in the workplace by arguing for a legal standard that considers the views of women when a court determines whether the harassment a female plaintiff encounters is severe or pervasive enough to constitute sexual harassment.